The Influence of Brand Equity and Brand Image on Purchase Intention of Kawasaki Brand in Mataram City - Putri Indriani; Sulhaini; Handry Sudiartha A (Indonesian Development Economics and Localities, 2025)
This study aims to determine the effect of Brand Equity and Brand Image on Purchase Interest in Kawasaki Products in Mataram City. The population of this study is all individuals who know Kawasaki products in Mataram City. The data collection method uses a survey sample. The data collection technique uses an online survey with a data collection tool, namely a questionnaire. In addition, this study uses a sample of 100 people who know Kawasaki products in Mataram City with a sampling method of purposive sampling. This type of research is associative causal. Data processing in this study uses SPSS 24.0 for windows by conducting validity tests, reliability tests, classical assumption tests, partial tests (t), coefficient of determination tests and multiple linear regression tests. The results of data analysis show that: (1) Brand Equity has a positive and significant effect on purchase interest, meaning that the higher the consumer perception of the brand, the greater their interest in buying the product. (2) Brand image has a positive and significant influence on purchasing interest. This means that if consumers have a good perception of the brand image, the brand is considered to be of high quality, trustworthy and in line with the brand's lifestyle, then they will be more interested and motivated to buy products from that brand.